2022
DOI: 10.1051/bioconf/20225400008
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting E-Smoking Behavior in Public Health Students of University Muhammadiyah Kalimantan Timur

Abstract: Background The trend of using electronic cigarettes (vapor) has developed rapidly among teenagers in the United States, and the largest increase occurred in the United States and Canada in 2018. The increased use of electronic cigarettes occurred from 2011 to 2015 while the decreased use occurred in 2016 and 2017. However, in 2018, the National Youth Tobacco Survey identified the increased use of vapor among adolescents; a 30-day trial of e-cigarette use increased by 20.8% among adolescents, especially student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…Our findings highlight the need for students in both countries to receive evidence-based education on e-cigarettes. The study identified variations in e-cigarette knowledge between Indonesia (75.6%) and China (87.4%), surpassing rates reported in previous studies in Hangzhou, China (42.6%) 32 , and in Indonesia (37.9%) 33 . This discrepancy may stem from potential differences in health literacy, particularly among the surveyed medical students.…”
Section: Discussioncontrasting
confidence: 55%
“…Our findings highlight the need for students in both countries to receive evidence-based education on e-cigarettes. The study identified variations in e-cigarette knowledge between Indonesia (75.6%) and China (87.4%), surpassing rates reported in previous studies in Hangzhou, China (42.6%) 32 , and in Indonesia (37.9%) 33 . This discrepancy may stem from potential differences in health literacy, particularly among the surveyed medical students.…”
Section: Discussioncontrasting
confidence: 55%
“…The study identi ed variations in e-cigarette knowledge between Indonesia (75.6%) and China (87.4%), surpassing rates reported in previous studies in Hangzhou, China (42.6%) [32] , Indonesia (37.9%) [33] . This discrepancy may stem from potential differences in health literacy, particularly among the surveyed medical students.…”
Section: Discussionmentioning
confidence: 57%